1991
DOI: 10.1210/jcem-73-3-533
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Supplementation Reduces Vertebral Bone Loss in Perimenopausal Women: A Controlled Trial in 248 Women between 46 and 55 Years of Age*

Abstract: To study the effect of calcium supplementation on perimenopausal bone loss, 295 women were randomized into a control group and 2 supplementation groups receiving, respectively, 1000 and 2000 mg elemental calcium/day for a period of 2 yr. We observed a significant decrease in lumbar bone loss in relation to the calcium supplementation (mean loss after 2 yr of 3.5% in the control group vs. 1.3% and 0.7% in the 1000 and 2000 mg groups, respectively), a significant increase in urinary calcium excretion, and a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0
4

Year Published

1992
1992
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(61 citation statements)
references
References 19 publications
4
53
0
4
Order By: Relevance
“…In studies which investigated the effects of supplementation on bone turnover, Elders et al [35] reported that bone turnover reduced after 1 year of calcium supplementation, while no changes in markers of bone metabolism have been observed by Rosen et al [36] after 1 year of calcium supplementation in early menopausal women. Supplementation of high soy protein is associated with lower level of bone resorption, but no changes in serum ALP in post-menopausal Japanese women as compared to calcium supplementation which had no influence on bone metabolism [37].…”
Section: Discussionmentioning
confidence: 99%
“…In studies which investigated the effects of supplementation on bone turnover, Elders et al [35] reported that bone turnover reduced after 1 year of calcium supplementation, while no changes in markers of bone metabolism have been observed by Rosen et al [36] after 1 year of calcium supplementation in early menopausal women. Supplementation of high soy protein is associated with lower level of bone resorption, but no changes in serum ALP in post-menopausal Japanese women as compared to calcium supplementation which had no influence on bone metabolism [37].…”
Section: Discussionmentioning
confidence: 99%
“…Factors affect the low blood calcium levels is inadequate vitamin D, low calcium intake or things that interfere with the absorption of calcium. The reason for calcium disabsorption may be due to the nutrients such as wheat in the form of bread, the a Refrence values in non pregnant women [10] staple cereal that is used daily by Iranian, which can impair intestinal calcium absorption, because of the presence of high amounts of phytic acid in wheat flour [30]. Vitamin D is essential for the maintenance of calcium homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Increased habitual calcium intake has been shown to lower bone turnover markers [16]. Although the beneficial effect of calcium supplementation is most marked in the first year of treatment, a slower, more cumulative effect is thought to occur in cortical bone [17,18].…”
Section: Discussionmentioning
confidence: 99%